A comparative study of CO2 refrigeration systems. (January 2019) - Bellos, Evangelos; Tzivanidis, Christos
Highlights: Different transcritical CO2 refrigeration systems are investigated. The use of mechanical subcooling is an effective way for increasing the COP. The use of an internal heat exchanger leads to small COP enhancements. The mean enhancement with the mechanical subcooling is 75.80%. The optimum maximum pressure is reduced in all the systems compared to the reference. Abstract: The refrigeration systems with CO2 seem to be attractive choices for the design of refrigeration systems with small environmental impact. The objective of this work is the comparison of different transcritical CO2 refrigeration systems and the determination of the most promising configurations. A typical system (evaporator, compressor, gas cooler, expansion valve) is the reference system and it is compared with a system with internal heat exchanger, a parallel compression system, a two-stage compression system and a system with mechanical subcooling after the gas collector. The examined systems produce refrigeration at one temperature level and they are examined for various operation scenarios. More specifically, the refrigeration temperature is examined from −35 °C to +5 °C, while the condenser temperature (or the gas cooler outlet temperature) from 35 °C to 50 °C. The analysis is conducted with developed models in Engineering Equation Solver (EES). According to the results, all the examined systems are more efficient than the reference system for all the examined scenarios. The system with the mechanical subcooling and the two-stage compression system are found to be the most efficient choices with a mean coefficient of performance enhancement at 75.8% and 49.8% respectively.